2017
DOI: 10.1038/s41598-017-09737-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the subthalamic nucleus does not negatively affect social cognitive abilities of patients with Parkinson’s disease

Abstract: Bilateral deep brain stimulation (DBS) of the subthalamic nucleus (STN) is a treatment option for patients with advanced idiopathic PD successful at alleviating disabling motor symptoms. Nevertheless, the effects of STN-DBS on cognitive functions remain controversial and few studies have investigated modification of social cognitive abilities in patients with PD treated with STN-DBS. Here we expanded the typically-investigated spectrum of these abilities by simultaneously examining emotion recognition, and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…Regarding the methodology of studies conducted so far, patients were tested in alternating experimental settings with stimulation ON or OFF and medication on or off, i.e., DBS ON/med on, DBS ON/med off, DBS OFF/med on, and DBS OFF/med off. Studies have either compared the pre- to postoperative condition after STN DBS within the same PD group [ 40 42 , 63 , 64 ], matched PD groups [ 44 , 48 , 49 ], or PD patients with matched HC [ 46 , 48 , 62 , 65 ]. Most studies reported impaired FER after STN DBS compared to before surgery [ 40 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the methodology of studies conducted so far, patients were tested in alternating experimental settings with stimulation ON or OFF and medication on or off, i.e., DBS ON/med on, DBS ON/med off, DBS OFF/med on, and DBS OFF/med off. Studies have either compared the pre- to postoperative condition after STN DBS within the same PD group [ 40 42 , 63 , 64 ], matched PD groups [ 44 , 48 , 49 ], or PD patients with matched HC [ 46 , 48 , 62 , 65 ]. Most studies reported impaired FER after STN DBS compared to before surgery [ 40 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the recognition of specific emotions (i.e., the seven basic emotions: happiness, surprise, fear, anger, sadness, disgust, and neutral), few studies showed a significant reduction of decoding accuracy for sadness [ 40 , 41 , 63 ], fear [ 41 , 42 , 44 , 63 ], anger [ 40 ], and a trend for disgust [ 40 ] after DBS compared to before, although there was not always a comparison with a HC group before surgery. Moreover, Enrici et al [ 48 ] showed a significant impairment of FER for surprise in the STN-DBS-PD group compared to the HC group. With regard to specific emotion performances in different stimulation conditions, Schroeder et al [ 43 ] showed impaired anger recognition in PD patients in the ON STN condition compared to the OFF condition, while Mondillon et al [ 62 ] found a significant decrease in the recognition of disgust ON STN stimulation and a tendency toward impaired recognition of fear OFF stimulation compared to HC (both off medication).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations